2002
DOI: 10.1152/ajpendo.00447.2001
|View full text |Cite
|
Sign up to set email alerts
|

Elevated endogenous cortisol reduces autonomic neuroendocrine and symptom responses to subsequent hypoglycemia

Abstract: . Elevated endogenous cortisol reduces autonomic neuroendocrine and symptom responses to subsequent hypoglycemia. Am J Physiol Endocrinol Metab 282: E770-E777, 2002. First published December 11, 2001 10.1152/ajpendo.00447.2001.-We tested the hypothesis that increased endogenous cortisol secretion reduces autonomic neuroendocrine and neurogenic symptom responses to subsequent hypoglycemia. Twelve healthy young adults were studied on two separate occasions, once after infusions of a pharmacological dose of ␣-(1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 34 publications
(74 reference statements)
2
48
0
Order By: Relevance
“…We believe that the contrasting conclusions of earlier glucocorticoid infusion studies may be related to the dose of steroid administered. While supraphysiologic hypercortisolemia (as achieved by McGregor et al [17]) may play a role in modulating sympathoadrenal responses to hypoglycemia, more moderate cortisol elevations (as achieved by Raju et al [18] and by our hydrocortisone infusion study, with cortisol responses closer to those typically observed during hypoglycemia) do not appear to exert a similar effect.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…We believe that the contrasting conclusions of earlier glucocorticoid infusion studies may be related to the dose of steroid administered. While supraphysiologic hypercortisolemia (as achieved by McGregor et al [17]) may play a role in modulating sympathoadrenal responses to hypoglycemia, more moderate cortisol elevations (as achieved by Raju et al [18] and by our hydrocortisone infusion study, with cortisol responses closer to those typically observed during hypoglycemia) do not appear to exert a similar effect.…”
Section: Discussionmentioning
confidence: 45%
“…However, the latter study's findings were complicated by profoundly suppressed epinephrine responses (Ͻ200 pg/ml or Ͼ60% lower than the epinephrine responses from our control studies) in the Addison's patients, present even during the control studies; this may have limited the ability of antecedent hypoglycemia to exert an additional effect. In a separate study, McGregor et al (17) showed that day 1 infusions of ␣-(1-24)-ACTH (producing high endogenous cortisol levels of 45 Ϯ 3 g/dl) also blunted day 2 catecholamine responses to hypoglycemia, lending additional support to antecedent hypercortisolemia as a possible mediator of HAAF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results have not been fully replicated. Another lab demonstrated cortisol-induced suppression of responses to hypoglycemia in human patients treated with high doses of adrenocorticotropic hormone to produce pharmacological cortisol levels (McGregor, Banarer, & Cryer, 2002). However, treatment with elevated levels of cortisol in the range normally measured during hypoglycemia did not reduce hypoglycemia-induced epinephrine secretion in a follow-up study (Raju, McGregor, & Cryer, 2003).…”
Section: Construct Validity Of Rodent Haaf Modelsmentioning
confidence: 99%
“…Most individual rhinoceroses (22 of 28) had glucose values .65 mg/dl at S2 (range of 14-168 mg/dl). In other species, hypoglycemia is partially mediated by the autonomic neuroendocrine system (McGregor et al, 2002). For example, in Standardbred horses exercised on a treadmill, cortisol concentrations increased along with glucose within 5 min postexercise (Valberg et al, 1989).…”
mentioning
confidence: 99%